2022
DOI: 10.1039/d2fo02087d
|View full text |Cite|
|
Sign up to set email alerts
|

Curcuminoids, a major turmeric component, have a sleep-enhancing effect by targeting the histamine H1 receptor

Abstract: Curcuminoids (curcumin, demethoxycurcumin, and bisdemethoxycurcumin), which are the major constituents of turmeric (Curcuma longa), have sleep-promoting effects in mice through blockade of histamine H1 receptors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As evident from previous studies, other constituents of GT with sleep-promoting effects could downregulate the arousal-inducing effects. The delta activity is used as a sleep parameter to evaluate sleep intensity in NREMS [ 43 , 44 ]. This study confirmed that caffeine did not change the delta activity [ 11 ] and that caffeine, as well as GT, induces arousal-inducing effects without a change in the delta activity.…”
Section: Discussionmentioning
confidence: 99%
“…As evident from previous studies, other constituents of GT with sleep-promoting effects could downregulate the arousal-inducing effects. The delta activity is used as a sleep parameter to evaluate sleep intensity in NREMS [ 43 , 44 ]. This study confirmed that caffeine did not change the delta activity [ 11 ] and that caffeine, as well as GT, induces arousal-inducing effects without a change in the delta activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the administration of curcuminoids (curcumin, demethoxycurcumin, and bisdemethoxycurcumin) to mice in pentobarbital‐induced sleep test modulated H 1 R activity, enhanced sleep duration, and NREM duration. They also decreased sleep latency without altering the REM and delta activity (Um et al, 2022).…”
Section: Herbal Sleep‐inducing Medicinesmentioning
confidence: 99%
“…Furthermore, the administration of curcuminoids reduced sleep latency and increased NREMS frequency in wild-type mice, but this effect was absent in H1R knockout mice [19]. Thus, curcuminoids and their constituents from C. longa roots reduced sleep latency and increased sleep duration by enhancing the quantity of non-rapid eye movement sleep (NREMS) by acting as modulators of histamine H1 receptor in the pentobarbital-induced sleep test in mice, indicating their usefulness in treating insomnia [19,20]. Ishola et al investigated the effects of administering C. longa rhizome to mice at varying doses (100, 200 or 400 mg/kg, p.o.)…”
Section: Introductionmentioning
confidence: 99%